Paradian Hotel Booking Mobile Application with QR Code for Check-In - Nor Zamrai, Nor Liyana; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2025)
This project focuses on developing a mobile application to streamline hotel reservations and check-ins for Paradian Hotel in Seremban. The current manual booking system leads to inefficiencies such as overbooking, long waiting times. By using Agile methodology, the application is designed with modules for registration, booking, payments, room management, and promotions. It incorporates Quick Response (QR) code technology for faster check-ins to optimize operations and marketing. The system enhances guest satisfaction, reduces errors, and improves efficiency, offering a modernized solution for hotel management.